Question #d4dce

2 Answers
Feb 23, 2018

Answer:

See below.

Explanation:

First, get rid of the fraction by multiplying everything by #x#

#2x^2 + 36000/x => 2x^3 +36000#

Now we take out the #HCF# of each term, in this case #2#

#2x^3+36000 => 2(x^3 + 18000)#

Feb 24, 2018

Answer:

#(2(x^3+18000))/x#

Explanation:

Let's set #y# to equal #2x^2+36000/x#

We have:

#y=2x^2+36000/x# Multiply both sides by #x#.

#xy=x(2x^2+36000/x)#Distribute

#xy=2x^3+36000#

#xy=2*x*x*x+2*2*2*2*2*3*3*5*5*5#

We ask ourselves: What do #2*x*x*x# and #2*2*2*2*2*3*3*5*5*5# share in common?

We see that they share a #2#

We factor. (Take out a two from each term)

#xy=2(x*x*x+2*2*2*2*3*3*5*5*5)#

#xy=2(x^3+18000)#

We now divide both sides by #x#.

#y=(2(x^3+18000))/x#

This is equal to what we started with (#2x^2+36000/x#) because they both equal #y#.

The answer is #(2(x^3+18000))/x#